2019
DOI: 10.1177/2309499019865954
|View full text |Cite
|
Sign up to set email alerts
|

The modified anterolateral approach to the humerus

Abstract: Introduction: The anterior and anterolateral approaches to the humerus describe splitting brachialis longitudinally, assuming its fibres run parallel to the shaft. Recent improvements in the understanding of brachialis anatomy however have demonstrated it has two distinct heads, with the bulk of its fibres running oblique relative to the humerus. Attempting to split brachialis longitudinally to the extent required for plate osteosynthesis invariably leads to transection of a significant number of muscle fibres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In the current study, the Constant scores and MEPS in group II (95.1 and 91.9, respectively) and group IV (94.4 and 91.1, respectively) were high, consistent with the excellent functional results reported by Chang et al [30]. In the current study, the rate of lateral antebrachial cutaneous nerve damage was 2.0%, similar to the results reported by Idoine et al [15].…”
Section: Bsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, the Constant scores and MEPS in group II (95.1 and 91.9, respectively) and group IV (94.4 and 91.1, respectively) were high, consistent with the excellent functional results reported by Chang et al [30]. In the current study, the rate of lateral antebrachial cutaneous nerve damage was 2.0%, similar to the results reported by Idoine et al [15].…”
Section: Bsupporting
confidence: 91%
“…The advantages of this approach include the supine positioning of the patient and the availability of distal and proximal extensions to achieve excellent exposure of the humeral shaft during surgery. Several retrospective clinical studies of patients with humeral diaphyseal fractures have reported no iatrogenic radial nerve palsy and high union rates after ORIF via the anterolateral approach [ 29 , 30 ]. Further, evidence suggests that during anterolateral surgery, patients are safer due to the supine position and the adequate exposure of the proximal and middle humeral shaft that can be achieved via this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have carried on retrospective studies and reported excellent functional outcomes via the posterior approach, with union rates of 90% to 100% [ 12 , 13 ]. Several retrospective clinical studies with humeral diaphyseal fractures have reported high union rates after ORIF via the anterolateral approach [ 20 , 21 ]. Our data showed that nonunion incidence was lower using anterolateral approach with two incisions compared to the posterior median approach.…”
Section: Discussionmentioning
confidence: 99%
“…The anterolateral approach can be used as an alternative to humeral midshaft fractures. The advantages of the anterolateral approach include the supine position and excellent imaging when the incision is extended proximally and distally [22].…”
Section: Type Of Incision P-value Posterior (N=29)mentioning
confidence: 99%